What is the best option to manage the bedside teaching for Neurology Clerkship -- Demonstration, Simulation or WeChat teaching? - Hongyan Zhou (MedEdPublish, 2020)
Background: Neurological clerkship is an important but challenging part of the neurology curriculum, and bedside teaching is essential for clerks to integrate complex theories and skills into practice.